Alternative monetary-policy instruments and limited credibility: An exploration - Javier Garcia-Cicco (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2022)
We evaluate the dynamics of a small and open economy under simple rules for alternative monetary-policy instruments, in a model with imperfectly anchored expectations. The inflation-targeting consensus indicates that interest-rate rules are preferred, instead of using either a monetary aggregate or the exchange rate as the main instrument; with arguments usually presented under rational expectations and full credibility. In contrast, we assume agents use econometric models to form inflation expectations, capturing limited credibility. In particular, we emphasize the exchange rate's role in shaping medium- and long-term inflation forecasts. We compare the dynamics after a shock to external-borrowing costs (arguably one of the most important sources of fluctuations in emerging countries) under three policy rules: a Taylor-type rule for the interest rate, a constant-growth-rate rule for monetary aggregates, and a fixed exchange rate. The analysis identifies relevant trade-offs in choosing among alternative instruments, showing that the relative merits of each of them is indeed influenced by how agents form inflation-related expectations.
Keywords: 330; Geldpolitik; Inflationserwartung; Glaubwürdigkeit; Kleine offene Volkswirtschaft; Theorie